Using the Cluster-Plus-Glue-Atom model to design the composition of low Young’s modulus β-Ti alloys for orthopaedic applications - Muchavi Noluntu; Raganya Lerato; Makhatha Elizabeth (MATEC Web of Conferences)
The design and development of metastable β-type Ti alloys with low Young’s moduli (E) requires the use of multiple β-phase stabilising alloying elements. The most commonly used alloy development design strategies do not provide accurate composition design. Moreover, the process of developing alloys is still based on empirical exploration, which is costly and time consuming. In this study, the cluster-plus-glue-atom (CPGA) model was employed in the composition design and interpretation of low-E, β-type Ti based alloys. Microstructure, phase analysis, Young’s modulus (mechanical testing and nano-indentation testing) of the as-cast alloys were investigated. The results demonstrated that the CPGA model was effective in formulating compositions which were able to simultaneously achieve high β-phase stability and low-E as exemplified by the [(Mo0.4Sn0.6) (Ti)14] (Nb)1 alloy which obtained a Young’s modulus of 59 GPa.